REDIM reduced chemistry for the simulation of counterflow diffusion flames with oscillating strain rates. Issue 4 (3rd July 2020) - Yu, Chunkan; Minuzzi, Felipe; Maas, Ulrich
Abstract : The dynamic behaviour and structures of laminar counterflow diffusion methane flames under oscillatory strain rates are investigated based on both detailed and reduced chemistry. It is known both from experiment and numerical studies that flame can deviate from its quasi-steady manner for high frequencies, which makes the well-known steady laminar flamelet model questionable. In this work, the Reaction-diffusion manifolds (REDIM) concept for simplified chemistry is applied to study the laminar counterflow diffusion flames with oscillating strain rates. In the construction of REDIM, one needs little knowledge of the studied system, and the REDIM reduced chemistry can cover both stable and unstable (extinction) regimes of the studied system. It is shown that the REDIM can capture both the steady and unsteady behaviours of the flame structures even for high frequencies, where the standard laminar steady flamelet approach is not appropriate.